ATM based passive optical network topology with VDSL as last mile drop-A study for highly dense localities - Rath, M.; Ranjan, N.; Sudarsan, S.D.; Ramamohan, T.R. (Optical Fiber Communications Conference: Post Conference Digest, 2002)
Out of available broadband access technologies, ATM-based passive optical network (APON) with very-high-speed digital subscriber line (VDSL) is a technically viable solution for the dense areas such as apartments or commercial complexes. They are scalable with off the shelf solutions already available. They promise to provide connectivity from 13 Mbps to 52 Mbps and as requirement goes beyond 100 Mbps over the next decade, APON could be extended to fibre-to-the-home (FTTH) by simple replacement of copper wire with fiber using ONUs.